Contesting the Discourse of Moderation: An Analysis of the MUI and Ministry of Religious Affairs’ Arguments on Interfaith Greetings - Favian, Rifqi; Arsyad, Hanafi (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2025)
I will examine the differences of opinion regarding interfaith greetings between MORA and MUI. Hence, I wish to address this issue in order to provide a reading in contested discourse and linking it with wasatiyya discourse. I shall do a critical discourse analysis using Norman Fairclough's theory. I will code data from each website (MUI and Kemanag) and news media to investigate the social and cultural background, as well as the three dimensions of discourse: texts, discursive practices, and social practices. Finally, I will look into the discourse production and consumption processes. As the result, MUI produced this discourse based on their ideological heritage that tends to securitize theological views that have a liberal tendency. However, in this issue of fatwa issued in 2004, MUI tends to foster more towards “respect in differences”. This is different from the Ministry of Religious Affairs which is more likely to embrace religious pluralism. For MUI and MORA, moderation is manifested in their respective concepts because they have similarities in respecting differences.